Informed Consent sebagai Perlindungan Hukum bagi Dokter dan Pasien dalam Langkah Antisipasi Potensi Terjadinya Sengketa Medis di Rumah Sakit - Annisa Fitira; Rahayu Subekti (Prosiding Seminar Nasional Ilmu Hukum, 2025)
Informed consent constitutes a fundamental legal and ethical requirement in healthcare services, ensuring that every medical action is performed with the patient’s full awareness and voluntary approval. In Indonesia, the obligation to obtain informed consent is firmly regulated under the Health Law No. 17 of 2023, the Minister of Health Regulation on Medical Consent, and provisions on medical records. This paper examines the essential role of informed consent as a protective instrument for both patients and healthcare providers within the clinical and legal framework. Informed consent guarantees patients’ rights to information, autonomy, and decision-making, while providing legal safeguards for medical practitioners by documenting the process of explanation, acceptance, or refusal of medical treatment. Proper documentation within medical records ensures accountability, continuity of care, and serves as crucial evidence when medical disputes arise. Medical disputes often stem from dissatisfaction, communication gaps, or misunderstandings about risks inherent in medical procedures. Therefore, informed consent functions not merely as an administrative requirement but as a mechanism for preventing conflict, clarifying responsibilities, and distinguishing unavoidable medical risks from professional negligence. By strengthening the implementation of informed consent, healthcare providers can enhance transparency, improve service quality, and reduce the likelihood of medical litigation.